Alternative control algorithm implementation for multirotor UAVs - Umar Mohammad (Nanyang Technological University, 2021)
The aim of this project is to assemble and build a small multirotor UAV, to study it, manipulate flight controller code on the UAV through software programming by using Raspberry Pi and understand the flight control software of a chosen open source flight control such as Ardupilot or PX4 and with a recommended weight of less than 5kg and able to sustain a flight time of more than 10 minutes and this design should have a rotational symmetry along all sides.